Learning Combinations Through â€œHandshakeâ€ - Ryandi, Rarri Bian; Somakim, Somakim; Susanti, Ely (Universitas Ahmad Dahlan, 2018)
This research used design research. It was constructing a learning trajectory through handshake context to help students’ understanding of the Combination concept. This research used PMRI approach. The participants of the research were the students of 10th class SMA Negeri 15 Palembang. For retrospective analysis, the data were collected from a teaching experiment in form of student’s work, field notes, and interviews. The obtained data is a learning trajectory which is consists of 1) students do a role-play scene of the handshake activity; this activity supports students’ understanding that A do handshake with B is the same with B do handshake with A, which it indicates order does not matter in Combination. 2) students utilize their knowledge about factorial forms to analyze the general pattern of the Combination. 3) students solve problems related to the Combination concept to help them think about how to solve the similar problems in the daily life. The results of the study showed that the use of the handshake context can help students to understand of the Combination concept.